2013
DOI: 10.1371/journal.pone.0080816
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Profiling of a Resistant vs. Susceptible Tomato (Solanum lycopersicum) Cultivar in Response to Infection by Tomato Yellow Leaf Curl Virus

Abstract: Tomato yellow leaf curl virus (TYLCV) threatens tomato production worldwide by causing leaf yellowing, leaf curling, plant stunting and flower abscission. The current understanding of the host plant defense response to this virus is very limited. Using whole transcriptome sequencing, we analyzed the differential gene expression in response to TYLCV infection in the TYLCV-resistant tomato breeding line CLN2777A (R) and TYLCV-susceptible tomato breeding line TMXA48-4-0 (S). The mixed inoculated samples from 3, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 82 publications
1
98
0
Order By: Relevance
“…Hence, expression variation is usually less pleiotropic and more directly visible to selection than coding variation (Wray, 2007; Galego Romero et al ., 2012). Recent studies have shown that variations in gene expression contribute to evolutionary changes in systems ranging from crop plants (Chen et al ., 2013; Koenig et al ., 2013) to animals and human diseases (Romero et al ., 2012). Through transcriptional variation and high outbreeding, tree populations may accumulate diverse alleles that enable adaptation to changing conditions over long periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, expression variation is usually less pleiotropic and more directly visible to selection than coding variation (Wray, 2007; Galego Romero et al ., 2012). Recent studies have shown that variations in gene expression contribute to evolutionary changes in systems ranging from crop plants (Chen et al ., 2013; Koenig et al ., 2013) to animals and human diseases (Romero et al ., 2012). Through transcriptional variation and high outbreeding, tree populations may accumulate diverse alleles that enable adaptation to changing conditions over long periods of time.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of a tomato WRKY gene in transgenic tobacco plants resulted in increased expression of defense genes and improved abiotic stress tolerance [57]. Furthermore, some tomato WRKY genes were found to show differential expression patterns after infection with viral, bacterial and fungal pathogens [55,[58][59][60] or treatment with pathogen-derived elicitors [61]. However, the biological functions for the majority of the tomato WRKYs are not clear yet.…”
Section: Introductionmentioning
confidence: 99%
“…Although the transcriptional modulation of LRR-RLK genes in response to virus infection has been reported for a number of plantviral pathosystems (Naqvi et al 2011;Mandadi and Scholthof 2012;Chen et al 2013;Czosnek et al 2013;Zheng et al 2013;Andolfo et al 2014), their possible role in antiviral defense remains speculative. These genes are induced by virus infection in most cases, but repression has In this study, we focused on SlSOBIR1, a tomato LRR-RLK implicated in plant immunity and described to be a crucial interactor for RLP-mediated resistance against fungal pathogens (Liebrand et al 2013a, b).…”
Section: Discussionmentioning
confidence: 99%